Rapid and visual Chlamydia trachomatis detection using loop‐mediated isothermal amplification and hydroxynaphthol blue. (21st November 2016) - Choopara, I.; Arunrut, N.; Kiatpathomchai, W.; Dean, D.; Somboonna, N.
Abstract: We developed an assay comprising crude DNA lysis by simple heat treatment coupled loop‐mediated isothermal amplification with hydroxynaphthol blue for Chlamydia trachomatis detection (petty patent pending), and evaluated the developed assay for its feasibility as a one‐step point‐of‐care detection on 284 endocervical swab specimens from clinically symptomatic C. trachomatis and healthy subjects. This assay is sensitive to 0·04 pg of ompA, specific with six primers targeting C. trachomatis ompA region, rapid (45 min total assay time), inexpensive (approx. 3 USD/reaction), does not require sophisticated instrumentation, and has comparable assay effectiveness (95% specificity, 90–100% sensitivity) to bacterial DNA isolation by a commercial kit coupled with polymerase chain reaction and gel electrophoresis (98–100% specificity, 87–100% sensitivity) based on the clinical samples test. The test result could be read by naked eye through the colour change from violet (negative) to sky blue (positive) for C. trachomatis ‐infected specimens. Further, this assay uses all safe chemical reagents and is hence safe to the users. Significance and Impact of the Study: Chlamydia trachomatis is the major bacterial sexually transmitted disease worldwide. The clinical symptoms are broad, and chronic C. trachomatis infections could lead to blindness, ectopic pregnancy, sterility in males and females, and a higher risk of the development of cervical cancer. The result indicates the potential usefulness of our crude DNA lysis coupled loop‐mediated isothermal amplification with hydroxynaphthol blue for a simple, rapid, specific, sensitive and cost‐effective assay for C. trachomatis detection from suspected specimens. This assay offers an alternative in the clinical diagnosis of C. trachomatis in resource‐limited health‐care facilities and clinical laboratories in developing countries, and in field tests. Abstract : Significance and Impact of the Study: Chlamydia trachomatis is the major bacterial sexually transmitted disease worldwide. The clinical symptoms are broad, and chronic C. trachomatis infections could lead to blindness, ectopic pregnancy, sterility in males and females, and a higher risk of the development of cervical cancer. The result indicates the potential usefulness of our crude DNA lysis coupled loop‐mediated isothermal amplification with hydroxynaphthol blue for a simple, rapid, specific, sensitive and cost‐effective assay for C. trachomatis detection from suspected specimens. This assay offers an alternative in the clinical diagnosis of C. trachomatis in resource‐limited health‐care facilities and clinical laboratories in developing countries, and in field tests.